Presentación: Dossier Experiencia y experimentación: metodologías cualitativas y audiovisuales para hacer etnografía hoy - Figueroa, Mercedes (2022)
Presentation by guest editors Maria Eugenia Ulfe, Mercedes Figueroa and Mauricio Godoy to the dossier on experience and experimentation, qualitative and audiovisual methodologies for doing ethnography today.